2015
DOI: 10.1371/journal.pone.0124408
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2.2 and Nkx2.9 Are the Key Regulators to Determine Cell Fate of Branchial and Visceral Motor Neurons in Caudal Hindbrain

Abstract: Cranial motor nerves in vertebrates are comprised of the three principal subtypes of branchial, visceral, and somatic motor neurons, which develop in typical patterns along the anteroposterior and dorsoventral axes of hindbrain. Here we demonstrate that the formation of branchial and visceral motor neurons critically depends on the transcription factors Nkx2.2 and Nkx2.9, which together determine the cell fate of neuronal progenitor cells. Disruption of both genes in mouse embryos results in complete loss of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…IEEs, like FBMNs and other branchial motor neurons, also express a collection of transcription factors that together assign a motor neuron identity. These genes include Isl1 (Ericson, Thor, Edlund, Jessell, & Yamada, ; Varela‐Echavarría, Pfaff, & Guthrie, ), Phox2a and Phox2b (Coppola, Pattyn, Guthrie, Goridis, & Studer, ; Pattyn et al, ; Tiveron, Pattyn, Hirsch, & Brunet, ), Nkx genes (most critically Nkx2‐2 , Nkx2‐9 , Nkx6‐1 , and Nkx6‐2 ) (Briscoe et al, ; Briscoe et al, ; Guthrie, ; Jarrar, Dias, Ericson, Arnold, & Holz, ; Müller, Jabs, Lorke, Fritzsch, & Sander, ; Pattyn et al, ), and Tbx20 (Ahn, Ruvinsky, Oates, Silver, & Ho, ; Kraus, Haenig, & Kispert, ; Song et al, ). Expression of these transcription factors is restricted to motor neuron progenitors as part of the broader SHH signaling network, with pMNv forming just ventral to the pMN domain, which produces somatic motor neurons (Dessaud, McMahon, & Briscoe, ; Jessell, ).…”
Section: Origin Specification and Migration Of Ocns Within The Braimentioning
confidence: 99%
See 1 more Smart Citation
“…IEEs, like FBMNs and other branchial motor neurons, also express a collection of transcription factors that together assign a motor neuron identity. These genes include Isl1 (Ericson, Thor, Edlund, Jessell, & Yamada, ; Varela‐Echavarría, Pfaff, & Guthrie, ), Phox2a and Phox2b (Coppola, Pattyn, Guthrie, Goridis, & Studer, ; Pattyn et al, ; Tiveron, Pattyn, Hirsch, & Brunet, ), Nkx genes (most critically Nkx2‐2 , Nkx2‐9 , Nkx6‐1 , and Nkx6‐2 ) (Briscoe et al, ; Briscoe et al, ; Guthrie, ; Jarrar, Dias, Ericson, Arnold, & Holz, ; Müller, Jabs, Lorke, Fritzsch, & Sander, ; Pattyn et al, ), and Tbx20 (Ahn, Ruvinsky, Oates, Silver, & Ho, ; Kraus, Haenig, & Kispert, ; Song et al, ). Expression of these transcription factors is restricted to motor neuron progenitors as part of the broader SHH signaling network, with pMNv forming just ventral to the pMN domain, which produces somatic motor neurons (Dessaud, McMahon, & Briscoe, ; Jessell, ).…”
Section: Origin Specification and Migration Of Ocns Within The Braimentioning
confidence: 99%
“…For IEEs and FBMNs, this means assuming a branchiovisceral fate within r4. The branchiovisceral fate is controlled by the combined action of NKX2‐2 and NKX2‐9 in progenitors within the pMNv domain (Jarrar et al, ). A key effector is the homeodomain protein PHOX2B, which promotes expression of Ascl1 and production of branchial and visceral motor neurons while inhibiting an alternative serotonergic fate (Dubreuil, Hirsch, Jouve, Brunet, & Goridis, ; Dubreuil, Hirsch, Pattyn, Brunet, & Goridis, ; Jacob et al, ; Pattyn et al, ; Pattyn, Hirsch, Goridis, & Brunet, ; Tiveron et al, ).…”
Section: Origin Specification and Migration Of Ocns Within The Braimentioning
confidence: 99%
“…CDP positive cells were arranged neatly in layers II‐IV, and FOXP2 positive cells were mainly expressed in layers V and VI (Figure 1d). We also tested the expression of transcription factor Nkx2.9 during cortical development (Holz et al., 2010; Jarrar et al., 2015). We found that the pyramidal cells could not express Nkx2.9 until P30 (Figure 1e), suggesting that it promoted the maturity of pyramidal cells in the neocortex.…”
Section: Resultsmentioning
confidence: 99%
“…Nkx2.2 −/− pups breath normally at birth but die on P6 from pancreatic insufficiency (59). Nkx2.2 has a primary role in ventral embryonic patterning (4), yet Nkx2.2 −/− animals do not generate defects in Phox2b ‐derived branchiomotor neurons, presumably through redundancy with Nkx2.9 (31). Our intersectional genetic studies show unequivocally that nVII shows derivation from both Phox2b and Nkx2.2 expressing cells.…”
Section: Discussionmentioning
confidence: 99%